Are There Personality Traits That Predispose Applicants to Fake Noncognitive Measures in Personnel Selection? - Tonković Grabovac, Maša (2012)
Previous research has shown that applicants’ faking on personality questionnaires could lower their predictive validity and reduce the quality of selection decisions. Hence, several models that specify key determinants of applicants’ faking responses on noncognitive measures have emerged. One of the common elements of these models is the important role of applicants’ personality in predicting their motivation to fake and consequently faking behavior. Nevertheless, this assumption lacks systematical empirical validation. The goal of the present study was to investigate the role of applicants’ personality facets in predicting the amount of faking on a noncognitive questionnaire. The total of 202 participants responded to personality inventory twice – first under instructions to respond honestly and afterwards under instructions to respond as an applicant in a simulated selection program. The difference between personality scores in two conditions represented the individual amount of faking, which was then regressed on the facet scores. As expected, the results confirmed significant contribution of Conscientiousness and Neuroticism facets in explaining the variance of faking. However, the most efficient predictors seem to be the facets of Openness. The obtained results provide support for personality traits having the important role in predicting applicants’ faking behavior on noncognitive measures in personnel selection.
Rad je nagrađen nagradom za mlade znanstvenike "Young Scientists’ Paper Awards" od strane organizacijskog odbora 10. međunarodne psihologijske znanstvene konferencije "Alpe-Adria".
Projekt MZOS
ENG